Paramedics’ Clinical Competence In Managing Diabetic Emergencies (The Review of Diabetic Studies, 2024)
Background:Saudi Arabia ranks among the highest worldwide in diabetes prevalence, creating a significant prehospital burden of diabetic emergencies such as hypoglycaemia, diabetic ketoacidosis (DKA), and hyperosmolar hyperglycaemic state (HHS). Paramedics are often the first responders to these life-threatening events, yet their competence and system support in the Saudi context remain insufficiently examined.Objective:This narrative review synthesizes international and local literature on paramedics’ clinical competence in managing diabetic emergencies and identifies strategies to strengthen prehospital care in Saudi Arabia.Methods:An integrative search was performed across PubMed, Scopus, and Google Scholar (2010–2025) using keywords related to paramedics, emergency medical services (EMS), diabetic emergencies, clinical competence, and Saudi Arabia. Studies addressing assessment, pharmacologic management, decision-making, education, or systems factors were included.Results:Thirty-eight relevant sources met the inclusion criteria. Global evidence emphasizes early point-of-care glucose testing, use of titrated D10 dextrose over D50 to prevent rebound hyperglycaemia, appropriate glucagon administration when IV access is delayed, and structured simulation-based training. Saudi EMS, primarily led by the Saudi Red Crescent Authority (SRCA), demonstrates growing infrastructure and training programs but lacks unified national protocols, standardized decision-support criteria, and outcome monitoring. Cultural and geographic challenges, such as rural response delays and limited continuing professional development (CPD), further constrain consistent competence.Conclusions:Saudi paramedics are positioned to play a critical role in improving outcomes for diabetic emergencies. Implementing a national Saudi Prehospital Diabetic Emergency Algorithm (SPDEA), mandating diabetes-specific CPD, and linking electronic patient care records to hospital data would enhance clinical competence, ensure consistent care delivery, and align with Vision 2030 health-sector transformation goals.